Pengaruh Beban Pajak Dan Resiko Bisnis Terhadap Struktur Modal - Rananda Septanta; Yunus Nurhasan; Chaeru Yahru Ramdani; Muhammad Eko Ariwibowo (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2022)
This tax research uses financial report data in companies listed on the Indonesian stock exchange. With the problem that there is not optimal tax revenue in Indonesia. This study examines whether there is influence from the influence of the tax burden so that efforts are needed to improve it to increase state revenue from the tax sector along with the existing variables, namely the variable tax burden, business risk on capital structure. This provides empirical evidence of the effect of tax burden and business risk both partially and simultaneously on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This research is a quantitative study using a purposive sampling technique based on predetermined criteria. The data analysis technique used is descriptive statistics, classic assumption test, and hypothesis testing. The results of research conducted based on the t test show that the tax burden has no effect on the capital structure, while business risk has an effect on the capital structure. The results of research conducted based on the f test, simultaneously tax burden and business risk affect the capital structure.